Sustainable rural development: an assessment of citizens' perception regarding the role of the planning framework within the Romanian local communities - Stan, Mari-Isabella; Cortel, Elena-Marinela (Technium Social Sciences Journal, 2022)
The development of local rural communities implies the creation of conditions for long-term economic development, while protecting the environment, as well as the preservation of traditional local culture. In order to ensure sustainable development at the local level, local public administration authorities must develop planning documents that are an effective tool to respond to some of the challenges they face. In this context, the purpose of this article is to carry out an assessment of the perception of the inhabitants of the Greci Municipality, located in Tulcea County, regarding the implementation of the Integrated Sustainable Development Strategy of the Greci Municipality. The analysis was carried out from the perspective of economic, social and environmental factors that must ensure the local sustainable rural development. The Sustainable Local Development Strategy creates an environment dedicated to strengthening the capacity of local authorities to implement projects for the development of the socio-economic sector that meet the needs of citizens.